PENGARUH KARAKTERISTIK DEMOGRAFI DAN KETIDAKPUASAN TERHADAP PERILAKU MENGELUH KONSUMEN PADA BENGKEL SERVICE SEPEDA MOTOR YAMAHA DIPONEGORO DENPASAR BALI - Handoyo, I Gede Suryana Ryan; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
The purpose of this study was to determine the effect of demographic characteristics and dissatisfaction with the behavior of consumers complained to the services Yamaha motorcycle repair shop service Diponegoro Denpasar. This research was conducted at the Workshop Service Yamaha is located at Jalan Diponegoro Denpasar-Bali This study used 10 indicators that the number of respondents who used this as a research sample of 100 people, using purposive sampling technique. Data collected by distributing questionnaires. Data analysis technique used is the chi-square analysis and simple linear regression analysis using SPSS 17 for windows. Based on the analysis shows the demographic characteristics significantly influence the behavior of consumers complained to the services repair shop service motorcycles Yamaha and dissatisfaction significantly positive effect on the behavior of consumers complained to the services Yamaha motorcycle repair shop service.
Keywords: Karakteristik Demografi; Ketidakpuasan; Perilaku Keluhan